Strategi Pengembangan Bahan Ajar Bahasa Arab untuk Penguatan Keterampilan Mendengar dan Berbicara Siswa Madrasah Ibtidaiyah - Mufti Rahman, Muh.; Abdul Hamzah, Andi (LP3M UNZAH GENGGONG, 2025)
This study aims to create audiovisual teaching resources to help students at Madrasah Ibtidaiyah improve their Arabic listening skills (mahārah al-istimā'). One of the four fundamental language skills for learning any foreign language, including Arabic, is listening. However, this ability frequently receives less emphasis during foundational learning. The literature study approach (literature review) used in this study attempts to gather information and examine various written sources pertinent to the studied subjects. According to the development results, students' comprehension of Arabic vocabulary, intonation, and sentence structure is greatly enhanced when audio-visual-based teaching materials are used. Furthermore, auditory media offers a more engaging and diversified educational experience. In order to effectively improve students' listening skills, audio-based teaching materials can be a creative approach to Arabic language instruction at Madrasah Ibtidaiyah.